Enabling RTK Positioning Under Jamming: Mitigation of Carrier-Phase Distortions Induced by Blind Spatial Filtering - Tobias Bamberg; Andriy Konovaltsev; Michael Meurer (Navigation, 2023)
New GNSS applications demand resilience against radio interference and high position accuracy. Separately, these demands can be fulfilled by multi-antenna systems using spatial filtering and carrier-phase positioning algorithms like real-time kinematic (RTK), respectively. However, combining these approaches encounters a severe issue: The spatial filtering induces a phase offset into the measured carrier phase leading to a loss of position accuracy. This paper presents a new approach to compensate for the phase offset in a blind manner (i.e., without knowing the antenna array radiation pattern or the direction of arrival of the signals). The proposed approach is experimentally validated in two jamming scenarios. One includes a jammer with increasing power and the other includes a moving jammer. The results demonstrate that the approach successfully compensates for the phase offset and, hence, allows for the combined use of RTK positioning and spatial filtering even under jamming.